Impact of Lantana camara in the Indian society - Chatterjee, Reshmi (International Journal of Environment, 2015)
Lantana camara, an introduced species by the British has turned itself in to a noxious weed, which has expanded itself in almost all the possible habitats of India. It is a major threat to the ecosystem, including plants and animals. Attempt to combat the further spread of this nuisance species has been of little help. Therefore, in the present discussion an attempt on its impact, toxicity, uses and therapeutic properties have been discussed. A carefully knitted plan should be framed emphasizing on exploiting this species economically as well as on taming the present threat so that the Indian society can be benefitted by properly utilizing the plant and thereby also conserve the ecosystem with its bio resources. The present review paper focuses on the various benefitting sides of the Lantana that would create better livelihood opportunities. DOI: http://dx.doi.org/10.3126/ije.v4i2.12663 International Journal of Environment Vol.4(2) 2015: 348-354